Mycelium- and root-derived C inputs differ in their impacts on soil organic C pools and decomposition in forests. (August 2018) - Zhang, Ziliang; Xiao, Juan; Yuan, Yuanshuang; Zhao, Chunzhang; Liu, Qing; Yin, Huajun
Abstract: While multiple lines of evidence suggests that root carbon (C) can significantly impact the soil organic C (SOC) pool and subsequent C cycles via rhizosphere priming effects, the relative magnitude of the effects that root- and fungal-derived C inputs have in driving the priming of SOC decomposition are currently unknown. In this study, we used ingrowth cores and stable C isotope analyses to quantify root- and mycelium-derived C sequestered in soil labile and recalcitrant C pools and their relative contributions to the decomposition of native SOC in a spruce-fir-dominated coniferous forest on the eastern Tibetan Plateau, China. The results showed that new C sequestered in the soil labile C pool was primarily (77%) from mycelium-derived C, while 60% of the root-derived C sequestered in the soil was incorporated into the recalcitrant pool. Furthermore, although the total native SOC pool was not significantly influenced by new C derived from both roots and mycelia, mycelium-derived C induced a remarkably greater negative priming effect (−12.0%) on the native labile C pool than did root-derived C (−5.8%); in contrast, mycelium-derived C induced a greater positive priming effect (13.8%) than root-derived C (7.1%) on the native recalcitrant C pool. Collectively, our findings suggest that mycelium-derived C make a greater contribution to the newly sequestered C in the soil labile C pool than root-derived C, thereby inducing a remarkably greater positive priming effect on the decomposition of native soil recalcitrant C. Therefore, mycelium-derived C inputs may play a dominant role in soil C dynamics and long-term C storage, at least in alpine forest ecosystems where ectomycorrhizal mutualisms dominate. Highlights: We quantified root- and mycelium-derived C into soil labile (LC) and recalcitrant C (RC) pools. Root- and mycelium-derived C are differently incorporated into soil LC and RC pools. Root C induced priming effects (PE) of opposite directions on decomposing native LC and RC. Mycelium-derived C induced greater PE on decomposing native soil organic C than root-derived C.